RADIATION AND TEMPERATURE GRADIENT DEPENDENT HEAT SOURCE EFFECTS ON MHD TRANSIENT FREE CONVECTION AND CHEMICALLY REACTIVE FLOW PAST A POROUS VERTICAL PLATE IN SLIP FLOW REGIME - Ravikumar, D. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The present paper deals with the analysis of unsteady free convection heat and mass transfer flow through a nonhomogeneous porous medium with variable permeability bounded by an infinite porous vertical plate in slip flow regime taking into account the radiation, chemical reaction and temperature gradient dependent heat source. The flow is considered under the influence of magnetic field applied normal to the flow. The permeability of the porous medium and the suction velocity at the plate decrease exponentially with time about a constant mean. Approximate solutions for velocity, temperature and concentration fields are obtained using perturbation technique. The expressions for skin-friction and rate of heat transfer and rate of mass transfer are also derived. The results obtained are discussed for cooling case (Gr>0) of the plate. The effects of various physical parameters, encountered into the problem, on the velocity field are numerically shown through graphs while the effects on skinfriction and rate of heat and mass transfer are numerically discussed with the help of tables. Keywords: MHD, Free convection, heat and mass transfer, radiation, non-homogeneous porous medium, temperature gradient dependent heat source and chemical reaction.